AB0565 Diffuse Alveolar Hemorrhage, Diagnosis, Treatment and 3-Year Prognosis in A Group of 32 Cases of Tertiary Centre. (15th July 2016) - Bradna, P.; Manak, J.; Soukup, T.; Toms, J.; Kodeda, M.
Abstract : Objectives: Diffuse alveolar hemorrhage (DAH) is severe, life-threatening syndrome, affecting the patients with systemic vasculitis and other systemic connective tissue diseases. It can be often the first manifestation of systemic disease. Frequently DAH is the acute incident, which often leads to the rapidly emerging respiratory and/or renal failure with requirement of ventilatory support and with high mortality rate. Methods: Diffuse alveolar hemorrhage was diagnosed on the basis of bronchoscopy and CT examination in patients with rapidly progressive respiratory insufficiency or newly emerged hemoptysis. Artificial ventilation was started in majority of cases.Therapeutically were used high doses of steroids i.v. (1000 mg 3–5 times in the iv infusion), Cyclophosphamide pulse, and plasmapheresis in some cases. Results: The group of patients consisted of 32 cases; the average age of patients was 54 years (20–71) years. In half of patients was the episode of DAH the first manifestation of the disease. 16 patients were pro3 ANCA-positive, 7 patients MPO-ANCA positive, 6 patient had known systemic connective tissue disease 46.8% of patients survive 3 years from the acute episode of DAH, including two with repeated hemorrhage. 15 patients died during the acute phase of the disease, 3 more died during next 3 years, two of them on an opportunistic infection. Steroids were used for all patients, cyclophosphamide in 71, plasmapheresis in 56%, and i.v. immunoglobulins for 6.25 percent of patients. Patients who survive 3 years after the acute episode, had significantly lower necessity of artificial ventilation (40 vs. 93%) against the fatal cases, unfavorable prognostic sign was long term connective tissue disease. Residual lung impairment is present in 53% of the surviving patients; the signs of pulmonary arterial hypertension are present in 20% of the surviving group. Conclusions: Diffuse alveolar hemorrhage is a sudden life-threatening event with a high mortality rate (46%) in the acute phase and during the first 3 years after the acute episode (20% of survivors). Up to half of patients the episode of DAH may be the first manifestation of the disease. Survival of patient depends on rapid diagnosis and the initiation of intensive immunosuppressive therapy. Respiratory failure is the major negative quoad vitam prognostic factor. Suspect the diffuse alveolar bleeding is necessary always in the case of a rapidly progressive respiratory failure. Acute bronchoscopy and x-ray examination give diagnosis of DAH, which further specify the acute examination of ANCA antibodies (71% of the report was ANCA antibodies positive. Disclosure of Interest: None declared